Use of Bubble Continuous Positive Airway Pressure (BCPAP) in Management of Neonatal Respiratory Distress Syndrome in Resource Limited Settings - Arzoo Idrees, Manzoor Ali Khan, Ishtiaq Ahmed Mughal, Mohsna Saeed Zia, Syed Zakir Hussain Shah, Khawaja Abrar Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the efficacy of use of bubble continuous positive airway pressure in management of neonatal respiratory distress syndrome. Study design: Prospective study. Place and duration of study: Paediatric Medicine, Abbas Institute of Medical Sciences (AIMS) Muzafarabad, AJ Kashmir from 01-02-2022 to 31-07-2022. Methodology: Fifty new born who were admitted with respiratory distress syndrome was enrolled. On clinical examination their shake test was found positive for respiratory distress syndrome or in other cases the chest x-ray imaging was suggestive towards respiratory distress syndrome symptoms. Oxygen flow-meter was prepared and nasal-pong were closed for bubble prior attachment with neonate. Appearance, pulse, grimace, activity and respiration scoring at five min, primigravida, child temperature, vital signs, oxygen saturation rate, complications, post and pre-bubble continuous positive airway pressure were recorded. Results: The mean age of the neonates was 2.7±1.1 days. There were more male children than female new born who were suffering from respiratory distress syndrome. The mean maternal age was 32.3±3.5 years with 70% of the births to be in singleton Antenatal steroids were received by 66.7% of new born and the 5 minutes appearance, pulse, grimace, activity and respiration score presented 64% new born within a range of 8-10 points. There were 76.2% respiratory distress syndromes new born who were successfully weaned off from bubble continuous positive airway pressure. Conclusion: Bubble continuous positive airway pressure is a cost-effective technique in resource limited regions for reducing and treating respiratory distress syndrome cases and decreasing mortality. Keywords: Management, Respiratory distress syndrome, Management